Bismuth and bismuth sulfide nanorod composite electrode material and preparation method and application thereof
By preparing bismuth and bismuth sulfide nanorod composite materials, the problems of limited selection and insufficient capacity of negative electrode materials for aqueous sodium ion batteries are solved, and electrochemical performance with high specific capacity and good cycle stability are achieved.
Patent Information
- Application Number
- CN202510477728.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-07-29
AI Technical Summary
The selection of negative electrode materials for existing aqueous sodium ion batteries is limited and the actual discharge capacity is relatively low, which limits the increase in battery energy density.
Using bismuth and bismuth sulfide nanorod composite material, a nanorod structure with a high specific surface area and one-dimensional electron transport channel is prepared by controlling the ratio of bismuth source to sulfur source and the solubilization of the solvent-thermal reaction conditions. The bonding layer interposer is embedded between the bismuth sulfide layers to form a dynamic equilibrium, and a uniform nanorod morphology is prepared.
The sodium storage performance of aqueous sodium ion batteries is significantly improved, providing high specific capacity and good cycle stability. The specific capacity of bismuth and bismuth sulfide nanorod composite material is 184.1mAh g-1 at 1A g-1 current density, and the capacity retention rate after 100 turns is 82.3%.
Smart Images

Figure CN120389009A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aqueous sodium ion batteries, and more specifically, relates to a bismuth and bismuth sulfide nanorod composite electrode material, a preparation method, and an application thereof. Background Art
[0002] In recent years, with the continuous increase in global energy demand and growing environmental awareness, the importance of energy storage battery technology in the energy sector has become increasingly prominent. Fossil fuels in the traditional energy mix are non-renewable and emit significant greenhouse gases, while solar and wind power generation is intermittent and unstable, posing significant challenges to the stability and reliability of the power grid. The development of energy storage battery technology can improve grid efficiency, enhance the utilization of renewable energy, promote the development of clean transportation, and contribute to the energy transition.
[0003] Lithium-ion batteries have become the mainstream energy storage solution due to their high energy density, long cycle life, and high efficiency. However, lithium-ion batteries may experience thermal runaway under high temperatures, overcharge, or physical damage, leading to fire or explosion. This safety hazard limits their application in some areas with high safety requirements. Aqueous sodium-ion batteries use aqueous solutions as electrolytes, which are inherently safe and avoid the risk of thermal runaway. In addition, aqueous batteries have low material costs, are environmentally friendly, and have abundant reserves, making them suitable for large-scale energy storage applications.
[0004] Only a few types of negative electrode materials have been reported in aqueous sodium-ion batteries, including vanadium oxides, phosphates, and organic materials. The negative electrode materials for aqueous sodium-ion batteries reported so far have the problems of low theoretical capacity and high voltage platform, which restricts the improvement of the energy density of aqueous sodium-ion batteries. For example, Zhang et al. synthesized a Na3MgTi(PO4)3 negative electrode material with a size of 5nm and rich mesoporous channels. Electrochemical tests showed that it could only provide 54mAh g at 0.2C charge and discharge. -1 Among organic materials, a new carbonyl organic salt, disodium naphthalene diimide, was reported, which exhibited a relatively low redox potential (-0.14 V vs. SHE), but the actual discharge capacity was only 53 mAh g -1 (DOI:10.1002 / aenm.201400133) These results indicate that existing aqueous sodium-ion battery anode materials have significant deficiencies in voltage and capacity characteristics, and that the development of new high-performance anode material systems is urgently needed. Summary of the Invention
[0005] In view of the above deficiencies or improvement requirements of the prior art, the present invention provides a composite electrode material of bismuth and bismuth sulfide nanorods, a preparation method thereof, and an application thereof, thereby solving the technical problems of limited selection of negative electrode materials and low actual discharge capacity in aqueous sodium-ion batteries.
[0006] To achieve the above object, according to one aspect of the present invention, a preparation method of a composite material of bismuth and bismuth sulfide nanorods is provided, including the following steps:
[0007] (1) After dissolving a bismuth source in an acid solution, a sulfur source is added for reaction, and the reaction solution is filtered to obtain bismuth sulfide; the molar ratio of bismuth element in the bismuth source to sulfur element in the sulfur source is 2:3 to 2:5;
[0008] (2) The bismuth sulfide and an intercalating agent are dissolved in an organic solvent to obtain a mixed solution, and then the mixture is subjected to a solvothermal reaction to cause the intercalating agent to be embedded between the layers of the bismuth sulfide and decompose to generate metallic bismuth. The molar ratio of the intercalating agent to the bismuth sulfide is controlled to be (10 - 50):1, and the reaction solution is filtered to obtain a nanorod composite material of a bismuth and bismuth sulfide mixture.
[0009] Preferably, the bismuth source is selected from one or more of bismuth nitrate pentahydrate, bismuth sulfate, and bismuth chloride, and more preferably bismuth nitrate pentahydrate.
[0010] Preferably, the sulfur source is selected from one or more of sodium sulfide, sodium thiosulfate, and thiourea, and more preferably sodium sulfide.
[0011] Preferably, the acid solution is selected from one or more of acetic acid, hydrochloric acid, sulfuric acid, and nitric acid.
[0012] Preferably, the intercalating agent is selected from one or more of lithium hydroxide, sodium hydroxide, and potassium hydroxide.
[0013] Preferably, the organic solvent is selected from one or more of ethylene glycol, ethanol, and isopropyl alcohol.
[0014] Preferably, in step (1), the temperature of the reaction is 25 - 40°C; in step (2), the temperature of the solvothermal reaction is 120°C - 200°C, and the reaction time is 6h - 24h.
[0015] Preferably, the filtration in steps (1) and (2) is specifically: suction filtration and washing are carried out using a mixed solution of water and ethanol, and then it is dried at 60 - 100°C.
[0016] According to another aspect of the present invention, a composite material of bismuth and bismuth sulfide nanorods prepared by the above-mentioned preparation method is provided.
[0017] According to another aspect of the present invention, a negative electrode plate for an aqueous sodium-ion battery is provided, comprising the bismuth and bismuth sulfide nanorod composite material, a conductive agent, and a binder.
[0018] Preferably, the mass ratio of the bismuth and bismuth sulfide nanorod composite material, the conductive agent, and the binder is (7-8):(1-2):1.
[0019] According to another aspect of the present invention, a method for preparing the negative electrode plate for the aqueous sodium-ion battery is provided. The specific steps are as follows: uniformly mix the bismuth and bismuth sulfide nanorod composite material with the conductive agent and the binder, then roll it into a sheet, and press it on a stainless steel mesh to obtain the negative electrode plate.
[0020] According to another aspect of the present invention, an aqueous sodium-ion battery is provided, comprising the negative electrode plate, and further comprising a reference electrode, a counter electrode, and an electrolyte; the electrolyte is a soluble sodium salt solution.
[0021] Generally speaking, compared with the prior art by the above technical solutions conceived by the present invention, the following beneficial effects can be achieved:
[0022] (1) The bismuth and bismuth sulfide nanorod composite material of the present invention has a high specific surface area, which is beneficial to increasing the active sites of the electrochemical reaction and improving the energy storage capacity; bismuth sulfide has a high sodium storage capacity, and metallic bismuth has high conductivity. By combining the two, the advantages of both high sodium storage capacity and high conductivity are realized, significantly improving the sodium storage performance of the aqueous sodium-ion battery.
[0023] (2) By adding an intercalating agent in the present invention, the alkali metal cations of the intercalating agent are intercalated between the two-dimensional layered material layers of bismuth sulfide, causing the original lattice of bismuth sulfide to collapse and the structure to reorganize to form metallic bismuth; by controlling the molar ratio of the intercalating agent to bismuth sulfide to be (10-50):1, the mutual conversion between bismuth sulfide and metallic bismuth is in a dynamic equilibrium, obtaining a composite phase of bismuth sulfide and metallic bismuth. And in the present invention, under the solvothermal reaction conditions, bismuth sulfide is partially intercalated to form a bismuth and bismuth sulfide nanorod composite material. This process has higher product uniformity compared with directly mixing bismuth and bismuth sulfide to obtain a mixture of the two, and a nanorod morphology with a uniform morphology can be obtained.
[0024] (3) By controlling the molar ratio of the bismuth element in the bismuth source to the sulfur element in the sulfur source to be 2:3-2:5 in the present invention, the intensity of this reaction is controlled, thereby generating bismuth sulfide with low crystallinity to improve the effect of subsequent intercalation with the intercalating agent.
[0025] (4) By controlling the solvothermal reaction temperature, the prepared bismuth and bismuth sulfide composite material is in a nanorod structure. The axial structure of the nanorods provides a one-dimensional electron transport channel, reducing the interfacial resistance. Additionally, the nanorod shape shortens the diffusion path of Na + , which can accelerate the reaction kinetics.
[0026] (5) When the bismuth and bismuth sulfide nanorod composite material of the present invention is used as the negative electrode of an aqueous sodium-ion battery, at a current density of 1 A g -1 , the specific capacity that can be provided is 184.1 mAh g -1 . After 100 cycles, the capacity retention rate is 82.3%, showing good cycle stability. When using pure bismuth sulfide as the negative electrode, at a current density of 1 A g -1 , the specific capacity that can be provided is 156.8 mAh g -1 . After 100 cycles, the capacity retention rate is 67.9%. Therefore, using the bismuth and bismuth sulfide nanorod composite material as the negative electrode of an aqueous sodium-ion battery exhibits good electrochemical performance. Description of the Drawings
[0027] Figure 1 XRD pattern of the bismuth and bismuth sulfide nanorod composite material prepared in Example 1.
[0028] Figure 2 SEM image of the bismuth / bismuth sulfide nanorod composite material prepared in Example 1.
[0029] Figure 3 Charge-discharge curve of the aqueous sodium-ion battery in Example 1 at a current density of 1.0 A g -1 .
[0030] Figure 4 Cycling performance test chart of the aqueous sodium-ion battery in Example 1 at a current density of 1.0 A g -1 .
[0031] Figure 5 XRD pattern of the bismuth / bismuth sulfide nanorod composite material prepared in Example 3.
[0032] Figure 6 SEM image of the bismuth / bismuth sulfide nanorod composite material prepared in Example 3.
[0033] Figure 7 Charge-discharge curve of the aqueous sodium-ion battery in Example 3 at a current density of 1.0 A g -1 .
[0034] Figure 8 Cycling performance test chart of the aqueous sodium-ion battery in Example 3 at a current density of 1.0 A g -1Cycling performance test chart at current density. Detailed implementation manner
[0035] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0036] Example 1
[0037] A preparation method of a bismuth and bismuth sulfide nanorod composite material includes the following steps:
[0038] (1) Dissolve 0.97 g of bismuth nitrate pentahydrate in a mixed solution of 100 mL of water and 9 mL of acetic acid, denoted as solution A. Then dissolve 0.23 g of anhydrous sodium sulfide in 30 mL of aqueous solution, denoted as solution B. Add solution B to solution A and stir for 2 h. Wash and filter by suction three times with ethanol and deionized water, and dry at 60 °C to obtain bismuth sulfide;
[0039] (2) Take 1 g of lithium hydroxide and dissolve it in 50 mL of ethylene glycol. Then take 0.4 g of bismuth sulfide and disperse it in the above solution. Transfer the solution to a high-pressure hydrothermal autoclave and carry out a solvothermal reaction at 200 °C for 24 h. Wash and filter the product by suction three times with ethanol and deionized water, and dry at 60 °C to obtain a bismuth and bismuth sulfide nanorod composite material.
[0040] Preparation of the electrode: Uniformly mix the bismuth sulfide and bismuth composite phase product with a conductive agent super P (conductive carbon black) and a binder PTFE (polytetrafluoroethylene) in a mass ratio of 7:2:1, roll it into a sheet, cut it into 8 mm round pieces, and press it on a stainless steel mesh under a pressure of 10 MPa to obtain an electrode sheet;
[0041] Use the prepared electrode sheet as the positive electrode, a saturated calomel electrode as the reference electrode, a Pt sheet as the counter electrode, and 1 M NaSO4 as the electrolyte to assemble a three-electrode cell. The test conditions are: the charge-discharge voltage window is -1.0 to 1.0 V (vs. SCE), and the charge-discharge current density is set to 1 A g -1 .
[0042] Figure 1 The XRD pattern of the bismuth and bismuth sulfide nanorod composite material prepared in Example 1 can be observed to have characteristic diffraction peaks of Bi2S3 and Bi, and the positions of each diffraction peak are completely consistent with the standard cards. And the peak shape is sharp, indicating good crystallinity. The above shows that the synthesized product is a composite phase of bismuth and bismuth sulfide with excellent crystallinity.
[0043] Figure 2 SEM image of the bismuth / bismuth sulfide nanorod composite material prepared in Example 1. The product shows a uniform nanorod-like morphology. These nanorods are about 100 - 200 nm in length and stack to form a three-dimensional porous aggregate.
[0044] Figure 3 For the aqueous sodium-ion battery in Example 1 at a current density of 1.0 A g -1 Charge-discharge curve at a current density. It shows a long discharge voltage plateau at -0.65 V, and the discharge specific capacity is 166.3 mAh g -1 .
[0045] Figure 4 For the aqueous sodium-ion battery in Example 1 at a current density of 1.0 A g -1 Cycling performance test chart at a current density. After 100 cycles, the capacity is 151.6 mAh g -1 , and the capacity retention rate is 82.3%, showing good cycling stability.
[0046] Example 2
[0047] A preparation method and battery application of a bismuth and bismuth sulfide nanorod composite electrode material are carried out according to the following steps:
[0048] (1) Dissolve 0.97 g of bismuth nitrate pentahydrate in a mixed solution of 100 mL of water and 9 mL of acetic acid, denoted as solution A. Then dissolve 0.23 g of anhydrous sodium sulfide in 30 mL of aqueous solution, denoted as solution B. Add solution B to solution A and stir for 2 h. Wash and filter by suction three times with ethanol and deionized water, and dry at 60 °C to obtain bismuth sulfide;
[0049] (2) Take 1 g of lithium hydroxide and dissolve it in 50 mL of ethylene glycol. Then take 0.1 g of bismuth sulfide and disperse it in the above solution. Transfer the solution to a high-pressure hydrothermal autoclave and carry out a solvothermal reaction at 180 °C for 24 h. Wash and filter the product by suction three times with ethanol and deionized water, and dry at 60 °C to obtain the bismuth / bismuth sulfide nanorod composite material.
[0050] (3) Uniformly mix the bismuth sulfide / bismuth composite phase product with a conductive agent and a binder in a ratio of 7:2:1, roll it into a sheet, cut it into 8 mm circular pieces, and press it on a stainless steel mesh under a pressure of 10 MPa to obtain an electrode sheet; Use the electrode sheet as the positive electrode, an Ag / AgCl electrode as the reference electrode, a Pt sheet as the counter electrode, and 1 M NaSO4 as the electrolyte to assemble a three-electrode battery.
[0051] Comparative Example 1
[0052] A preparation method and battery application of a bismuth sulfide electrode material, characterized in that it is carried out according to the following steps:
[0053] (1) Dissolve 0.97 g of bismuth nitrate pentahydrate in a mixed solution of 100 mL of water and 9 mL of acetic acid, denoted as solution A. Then dissolve 0.23 g of anhydrous sodium sulfide in 30 mL of aqueous solution, denoted as solution B. Add solution B to solution A and stir for 2 h. Wash and filter by suction three times with ethanol and deionized water, and dry at 60 °C to obtain bismuth sulfide.
[0054] Preparation of the electrode sheet: Uniformly mix the bismuth sulfide obtained in step (1) with a conductive agent and a binder in a ratio of 7:2:1, roll it into a sheet, cut it into 8-mm circular pieces, and press it onto a stainless steel mesh under a pressure of 10 MPa to obtain the electrode sheet.
[0055] Use the said electrode sheet as the positive electrode, a saturated calomel electrode as the reference electrode, a Pt sheet as the counter electrode, and 1 M NaSO4 as the electrolyte to assemble a three-electrode cell. The test conditions are as follows: the charge-discharge voltage window is -1.0 to 1.0 V (vs. SCE), and the charge-discharge current density is set to 1 A g -1 .
[0056] Figure 5 XRD pattern of the bismuth / bismuth sulfide nanorod composite material prepared in Example 3. The bulging peak at 20 - 30° corresponds to Bi2S3, indicating that low-crystalline Bi2S3 is synthesized.
[0057] Figure 6 SEM image of the bismuth / bismuth sulfide nanorod composite material prepared in Example 3. The figure shows that the obtained product is mainly composed of irregular blocky particles with a size distribution in the range of dozens to hundreds of nanometers, and the regularity and uniformity are relatively poor.
[0058] Figure 7 Charge-discharge curve of the aqueous sodium-ion battery in Example 3 at a current density of 1.0 A g -1 shows two main discharge voltage platforms at -0.65 V and 0.95 V, and the discharge specific capacity is 102.4 mAh g -1 .
[0059] Figure 8 Charge-discharge curve of the aqueous sodium-ion battery in Example 3 at a current density of 1.0 A g -1 shows that the capacity increases rapidly during the initial cycling process, reaches the highest specific capacity at the 10th cycle, which is 156.8 mAh g -1 , and the capacity is 106.5 mAh g after 100 cycles -1 , and the capacity retention rate is only 67.9%.
[0060] Those skilled in the art can easily understand that the above are only the preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention should be included within the protection scope of the present invention.
Claims
1. A preparation method of a bismuth and bismuth sulfide nanorod composite material, characterized in that It includes the following steps: (1) After dissolving the bismuth source in an acid solution, a sulfur source is added for reaction, and the reaction solution is filtered to obtain bismuth sulfide; the molar ratio of bismuth element in the bismuth source to sulfur element in the sulfur source is 2:3 to 2:5; (2) The bismuth sulfide and the intercalant are dissolved in an organic solvent to obtain a mixed solution, and then the mixture is subjected to a solvothermal reaction to cause the intercalant to be embedded in the interlayer of the bismuth sulfide and decompose to generate metallic bismuth. The molar ratio of the intercalant to the bismuth sulfide is controlled to be (10 - 50):1, and the reaction solution is filtered to obtain a nanorod composite material of bismuth and bismuth sulfide mixture.
2. The preparation method of a bismuth and bismuth sulfide nanorod composite material according to claim 1, characterized in that, The bismuth source is selected from one or more of bismuth nitrate pentahydrate, bismuth sulfate, and bismuth chloride, preferably bismuth nitrate pentahydrate; The sulfur source is selected from one or more of sodium sulfide, sodium thiosulfate, and thiourea, preferably sodium sulfide.
3. The preparation method of a bismuth and bismuth sulfide nanorod composite material according to claim 1, characterized in that, The acid solution is selected from one or more of acetic acid, hydrochloric acid, sulfuric acid, and nitric acid; The intercalant is selected from one or more of lithium hydroxide, sodium hydroxide, and potassium hydroxide; The organic solvent is selected from one or more of ethylene glycol, ethanol, and isopropyl alcohol.
4. The preparation method of a bismuth and bismuth sulfide nanorod composite material according to claim 1, characterized in that, In step (1), the temperature of the reaction is 25 - 40 °C; in step (2), the temperature of the solvothermal reaction is 120 °C - 200 °C, and the reaction time is 6 h - 24 h.
5. The preparation method of a bismuth and bismuth sulfide nanorod composite material as claimed in claim 1, wherein, The filtration in steps (1) and (2) specifically is: suction filtration and washing are carried out with a mixed solution of water and ethanol, and then it is dried at 60 - 100 °C.
6. A nanorod composite material of bismuth and bismuth sulfide prepared by the preparation method according to any one of claims 1 - 5.
7. A negative electrode sheet of an aqueous sodium-ion battery, characterized in that, It includes the nanorod composite material of bismuth and bismuth sulfide according to claim 6, a conductive agent, and a binder.
8. The negative electrode sheet of a sodium-ion aqueous battery according to claim 7, characterized in that, The mass ratio of the nanorod composite material of bismuth and bismuth sulfide, the conductive agent, and the binder is (7 - 8):(1 - 2):
1.
9. A method for preparing a negative electrode sheet of an aqueous sodium-ion battery according to any one of claims 7 to 8, characterized in that, The specific steps are: the nanorod composite material of bismuth and bismuth sulfide according to any one of claims 7 - 8 is uniformly mixed with the conductive agent and the binder, and then rolled into a sheet and pressed on a stainless steel mesh to obtain the negative electrode sheet.
10. Aqueous sodium-ion battery, characterized in that, It includes the negative electrode sheet according to any one of claims 7 - 8, and also includes a reference electrode, a counter electrode, and an electrolyte; the electrolyte is a soluble sodium salt solution.